2012
DOI: 10.1111/j.1747-0285.2012.01378.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification In Silico and In Vitro of Novel Trypanosomicidal Drug‐Like Compounds

Abstract: Atom-based bilinear indices and linear discriminant analysis are used to discover novel trypanosomicidal compounds. The obtained linear discriminant analysis-based quantitative structure-activity relationship models, using non-stochastic and stochastic indices, provide accuracies of 89.02% (85.11%) and 89.60% (88.30%) of the chemicals in the training (test) sets, respectively. Later, both models were applied to the virtual screening of 18 in-house synthesized compounds to find new pro-lead antitrypanosomal age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 46 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…According to these facts, we evaluated the effectiveness of derivatives 22 and 24 upon the three main forms of T. cruzi Y strain, which is routinely used in our laboratories for in vitro and in vivo drug screening models (Castillo-Garit, et al 2012; da Silva et al 2012; Araújo et al 2014; Fonseca-Berzal et al 2015). The trypanocidal profile both prototypes accomplished on this strain was quite similar to that of over CL-B5 parasites (Vega et al 2012; Fonseca-Berzal et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to these facts, we evaluated the effectiveness of derivatives 22 and 24 upon the three main forms of T. cruzi Y strain, which is routinely used in our laboratories for in vitro and in vivo drug screening models (Castillo-Garit, et al 2012; da Silva et al 2012; Araújo et al 2014; Fonseca-Berzal et al 2015). The trypanocidal profile both prototypes accomplished on this strain was quite similar to that of over CL-B5 parasites (Vega et al 2012; Fonseca-Berzal et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…trypomastigotes and amastigotes) must be carried out in vitro before advancing compounds to in vivo assays (Romanha et al 2010), since different drug susceptibility can be registered among different stages from the same T. cruzi stock (Moraes et al 2014). According to these facts, we evaluated the effectiveness of derivatives 22 and 24 upon the three main forms of T. cruzi Y strain, which is routinely used in our laboratories for in vitro and in vivo drug screening models (Castillo-Garit, et al 2012;da Silva et al 2012;Araújo et al 2014;Fonseca-Berzal et al 2015). The trypanocidal profile both prototypes accomplished on this strain was quite similar to that of over CL-B5 parasites (Vega et al 2012;Fonseca-Berzal et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…To test whether this in vitro Ufm1 processing activity of the recombinant Ufsp can be inhibited by the anti-parasitic drugs that are commonly in use, and thus to verify if Ufsp activity is amenable to inhibition we tested a limited set of the anti-parasitic drugs in our assay. We tested Nifurtimox, Amphotericin B, Melarprosol, and Geramin following the doses most commonly used in in vitro studies [23][26]. Results showed that Nifurtimox, Melarprosol, and Geramin did not inhibit Ufm1 processing activity at the concentrations tested (low, medium and high, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…"In silico" methods are useful tools for screening chemicals, especially in early stages of the drug discovery process [5][6][7][8]. In the last two decades these studies have played a fundamental role in the development of a number of drugs that are currently on the market [9].…”
Section: Introductionmentioning
confidence: 99%